A half a century of measuring ungulate body condition using indices: is it time for a change? - Serrano, E. (2012)
From a literature review of five wildlife ecology journals since 1937, we document how using indices to monitor ungulate body condition is common practice, with the kidney fat index (KFI = weight of fat around the kidneys/weight of kidneys without fat × 100) as the favoured tool (82% of studies). In this context, we highlight the problems of using indices when underlying statistical assumptions are not met (isometry, parallel slopes between treatments). We show, with real and simulated data for two cervids with contrasting fat storage strategies, how results from analysis of variance of KFI values differ from analysis of covariance (ANCOVA) of raw data. We conclude that the KFI is affected by the restrictions typically associated with derived index values, and as a consequence, statistical analysis of the KFI could generate spurious results leading to erroneous interpretations concerning variation in body condition of ungulate populations. Thus, we recommend analysing fat weight as an untransformed variable in ANCOVA (kidney weight as covariate) to describe body condition variation in ungulates.